PENGHENTIAN PENYIDIKAN DAN PENUNTUTAN TINDAK PIDANA KORUPSI OLEH KPK: SEBUAH PENELUSURAN TEORETIS: Termination of Investigation and Prosecution of Corruption Crimes by The KPK: A Theoretical Exploration - Ahwan, Ahwan; Ristanti, Yuni (Ganec Swara, 2025)
The termination of investigation and prosecution of corruption crimes is one of the important substances of the amendment to Law Number 19 of 2019 concerning the Corruption Eradication Commission. The emergence of this mechanism in the KPK's authority triggered discourse in the academic realm and legal practice. Naturally, because this mechanism was previously one of the special elements owned by the KPK that excluded the provisions of the codification of criminal procedure law (KUHAP). This article takes a place as a supporter with the basis of argumentation on the theoretical aspects and urgency of the mechanism for terminating investigations and prosecutions by the KPK. This paper uses a normative legal research method that entirely uses legal materials obtained through literature studies. The results show that the termination of investigation and prosecution of corruption crimes is based on the sunrise principle and sunset principle as well as the shield function and the sword function as well as the principle of realistic prospect of conviction which in its implementation has two filters, namely evidential sufficiency and public interest. From a theoretical perspective, the termination of investigation and prosecution can be traced from the integrative theory. This theory is described as a basis that provides balance in criminal procedure law and is sourced from customary law and the way of life of Indonesian society. In terms of urgency, the authority to terminate investigations and prosecutions provides additional alternatives for the KPK in handling corruption crimes, especially in realizing legal certainty and the principle of speedy trial in criminal procedure law.